Inferring the IGM thermal history during reionisation with the Lyman-α forest power spectrum at redshift z ≃ 5 - Nasir, Fahad; Bolton, James S.; Becker, George D. (Oxford University Press, 2016)
We use cosmological hydrodynamical simulations to assess the feasibility of constraining the thermal history of the intergalactic medium during reionisation with the Lyα forest at z ≃ 5. The integrated thermal history has a measureable impact on the transmitted flux power spectrum that can be isolated from Doppler broadening at this redshift. We parameterise this using the cumulative energy per proton, u₀, deposited into a gas parcel at the mean background density, a quantity that is tightly linked with the gas density power spectrum in the simulations. We construct mock observations of the line of sight Lyα forest power spectrum and use a Markov Chain Monte Carlo approach to recover u₀ at redshifts 5≲z≲12. A statistical uncertainty of ∼ 20 per cent is expected (at 68 per cent confidence) at z ≃ 5 using high resolution spectra with a total redshift path length of Δz = 4 and a typical signal-to-noise ratio of S/N = 15 per pixel. Estimates for the expected systematic uncertainties are comparable, such that existing data should enable a measurement of u₀ to within ∼ 30 per cent. This translates to distinguishing between reionisation scenarios with similar instantaneous temperatures at z ≃ 5, but with an energy deposited per proton that differs by 2–3eV over the redshift interval 5≲z≲12. For an initial temperature of T ∼ 10⁴K following reionisation, this corresponds to the difference between early (zre = 12) and late (zre = 7) reionisation in our models.